A NiS2 / MoS2 / CdS nanowire and its preparation method and application
By loading NiS2/MoS2 complex on the CdS nanowires, NiS2/MoS2/CdS nanowires are formed, which solves the problem of low electron and hole separation efficiency of CdS photocatalysts, and significantly improves its photocatalytic activity and performance.
Patent Information
- Application Number
- CN202310094195.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-10
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-02-10
AI Technical Summary
The existing CdS photocatalysts have low separation efficiency of photogenerated electrons and photogenerated holes, resulting in insufficient photocatalytic activity.
By loading NiS2/MoS2 complexes on the CdS nanowires, NiS2/MoS2/CdS nanowires are formed, and the heterojunction in the complex and the active sites of NiS2 are used to improve the separation efficiency between electrons and holes.
The photocatalytic activity of NiS2/MoS2/CdS nanowires was significantly improved, and their performance in decomposing water to produce hydrogen and degrading organic pollutants was enhanced. The hydrogen production performance reached 8542μmol·g-1·h-1, with a degradation rate of 76% to 93%.
Smart Images

Figure CN116212899B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalysis, and specifically relates to a NiS2 / MoS2 / CdS nanowire and a preparation method and application thereof. Background Art
[0002] Hydrogen energy, as a green energy with high calorific value and renewable energy, is a new energy that fully meets the current priority for energy issues and has gradually attracted people's attention. Solar energy is an inexhaustible, renewable and pollution-free energy. However, solar energy has disadvantages such as low energy density, discontinuity and instability, which limits its wide application. Photocatalytic semiconductor technology, as a new green chemical technology, can reasonably develop and apply solar energy. Therefore, the development of photocatalytic technology and the preparation of suitable photocatalytic materials are the only choice to solve the problems of energy scarcity and water pollution.
[0003] As a typical photocatalyst, cadmium sulfide has a bandgap of only 2.4eV and is a visible light responsive photocatalyst. Furthermore, CdS has a suitable energy band position and can meet the thermodynamic conditions of various photocatalytic reactions. However, the separation efficiency of photogenerated electrons and photogenerated holes of CdS is poor. In order to improve the separation efficiency of photogenerated electrons and photogenerated holes, and thus enhance the photocatalytic activity of CdS, many modification methods have been adopted, such as: 1. Morphology and structure regulation; 2. Defect strategy; 3. Metal doping. However, the photocatalytic activity of CdS still needs to be further improved. Summary of the invention
[0004] The purpose of the present invention is to provide a NiS2 / MoS2 / CdS nanowire and a preparation method and application thereof. The NiS2 / MoS2 / CdS nanowire of the present invention has high photocatalytic activity.
[0005] The invention provides a NiS2 / MoS2 / CdS nanowire, comprising a CdS nanowire and a NiS2 / MoS2 composite loaded on the CdS nanowire; the NiS2 / MoS2 composite comprises NiS2 and MoS2.
[0006] Preferably, the loading amount of the NiS2 / MoS2 composite is 35-50wt%; the molar ratio of NiS2 to MoS2 in the NiS2 / MoS2 composite is 1:0.2-3.
[0007] Preferably, the length of the NiS2 / MoS2 / CdS nanowire is 2 to 5 μm and the diameter is 150 to 200 nm.
[0008] The present invention also provides a method for preparing the NiS2 / MoS2 / CdS nanowires described in the above scheme, comprising the following steps:
[0009] The cadmium chloride solution and the sodium diethyldithiocarbamate solution are mixed to carry out a complex reaction to obtain a cadmium complex;
[0010] The cadmium complex is mixed with ethylenediamine to undergo a solvothermal reaction to obtain CdS nanowires;
[0011] The CdS nanowires, nickel nitrate, ammonium molybdate, hexamethylenetetramine and water are mixed and subjected to a hydrothermal reaction to obtain Ni(OH)2 / MoO2 / CdS nanowires;
[0012] The Ni(OH)2 / MoO2 / CdS nanowires are co-calcined with sulfur to obtain the NiS2 / MoS2 / CdS nanowires.
[0013] Preferably, the mass ratio of cadmium chloride in the cadmium chloride solution to sodium diethyldithiocarbamate in the sodium diethyldithiocarbamate solution is 0.06-4:1.
[0014] Preferably, the mass ratio of the CdS nanowires to nickel nitrate is 1:0.175-10;
[0015] The mass ratio of the CdS nanowires to ammonium molybdate is 1:0.2-12;
[0016] The mass ratio of the CdS nanowires to hexamethylenetetramine is 1:2-4.
[0017] Preferably, the temperature of the solvent thermal reaction is 160-200° C. and the time is 22-26 hours.
[0018] Preferably, the temperature of the hydrothermal reaction is 130-170° C., and the time is 8-12 hours.
[0019] Preferably, the co-calcination temperature is 350-450° C., and the holding time is 0.5-1.5 h.
[0020] The present invention also provides the use of the NiS2 / MoS2 / CdS nanowires described in the above scheme or the NiS2 / MoS2 / CdS nanowires prepared by the preparation method described in the above scheme as catalysts in decomposing water to produce hydrogen or degrading organic pollutants.
[0021] The present invention provides a NiS2 / MoS2 / CdS nanowire, comprising a CdS nanowire and a NiS2 / MoS2 composite loaded on the CdS nanowire; the NiS2 / MoS2 composite comprises NiS2 and MoS2. Under visible light irradiation, CdS and MoS2 generate electrons (e) in their conduction band and valence band, respectively. - ) and holes (h +). The conduction band of CdS is more negative than that of MoS2 and MoS2 has a high electron transfer efficiency, so that the heterojunction formed by the combination of CdS and MoS2 accelerates the transfer of electrons from the conduction band of CdS to the conduction band of MoS2, thereby improving the separation efficiency of electrons and holes, and further improving the photocatalytic activity. In addition, the electrons excited on the conduction band of MoS2 and the remaining electrons on the conduction band of CdS will be captured by NiS2, thereby inhibiting the recombination of electrons and holes in NiS2 / MoS2 / CdS nanowires, further improving the separation efficiency of electrons and holes. In addition, in the process of capturing electrons, NiS2 will also provide active sites for the reaction, which further improves the photocatalytic activity of NiS2 / MoS2 / CdS nanowires. At the same time, the untransferred electrons of MoS2 can recombine with the holes generated by the valence bands of CdS and MoS2 to prevent the recombination of the transferred electrons and holes, thereby improving the electron transfer rate, or being transmitted to the surface and consumed by the sacrificial agent, thereby improving the electron transfer rate and further improving the photocatalytic activity. The results of the embodiment show that the NiS2 / MoS2 / CdS nanowires of the present invention have a hydrogen production performance of 8542 μmol·g when catalyzing water decomposition to produce hydrogen. -1 ·h -1 ; Within 90 minutes, the degradation rate of antibiotic active red 2 was 76% to 93%.
[0022] The preparation method of the present invention is simple and low in cost. In the prepared NiS2 / MoS2 / CdS nanowires, the NiS2 / MoS2 complex grows tightly on the surface of the CdS nanowires, which makes the NiS2 / MoS2 / CdS nanowire catalyst have high cyclic stability in photocatalytic water decomposition to produce hydrogen and photocatalytic degradation.
[0023] Furthermore, the present invention also prepares NiS2 / MoS2 / CdS nanowires with uniform size by carrying out the complexation reaction under stirring conditions, mixing CdS nanowires, nickel nitrate, ammonium molybdate and water and then mixing with hexamethylenetetramine. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the XRD pattern of NiS2 / MoS2 / CdS nanowires in Example 10;
[0025] Figure 2 The performance results of water decomposition and hydrogen production of NiS2 / MoS2 / CdS nanowires in Example 3;
[0026] Figure 3 The degradation rates of different antibiotics by NiS2 / MoS2 / CdS nanowires in Example 3;
[0027] Figure 4 The cycling test results of NiS2 / MoS2 / CdS nanowires in Example 3;
[0028] Figure 5 This is the SEM image of NiS2 / MoS2 / CdS nanowires in Example 10;
[0029] Figure 6 This is a high-resolution transmission electron microscopy image of the NiS2 / MoS2 / CdS nanowires of Example 10;
[0030] Figure 7 This is a comparison chart of the photocatalytic hydrogen production of CdS nanowires, NiS2 / MoS2 / CdS nanowires in Example 3, NiS2 / CdS nanowires in Comparative Example 1, and NiS2 / MoS2 in Comparative Example 2. DETAILED DESCRIPTION
[0031] The invention provides a NiS2 / MoS2 / CdS nanowire, comprising a CdS nanowire and a NiS2 / MoS2 composite loaded on the CdS nanowire; the NiS2 / MoS2 composite comprises NiS2 and MoS2.
[0032] In the present invention, the morphology of the NiS2 / MoS2 composite is preferably flaky, and the size of the NiS2 / MoS2 composite is preferably 30-50 nm; the molar ratio of NiS2 to MoS2 is preferably 1:0.2-3, more preferably 1:0.5-2, and further preferably 1:1-1.5; the loading amount of the NiS2 / MoS2 composite is preferably 35-50 wt%, more preferably 40-45 wt%. In the present invention, the length of the NiS2 / MoS2 / CdS nanowire is preferably 2-5 μm, more preferably 3-4 μm; the diameter is preferably 150-200 nm, more preferably 160-180 nm.
[0033] Under visible light irradiation, CdS and MoS2 generate electrons in their conduction band and valence band, respectively. - ) and holes (h +). The conduction band of CdS is more negative than that of MoS2 and MoS2 has a high electron transfer efficiency, so that the heterojunction formed by the combination of CdS and MoS2 accelerates the transfer of electrons from the conduction band of CdS to the conduction band of MoS2, thereby improving the separation rate of electrons and holes and the photocatalytic activity. In addition, the electrons excited on the conduction band of MoS2 and the remaining electrons on the conduction band of CdS will be captured by NiS2, thereby inhibiting the recombination of electrons and holes in NiS2 / MoS2 / CdS nanowires, which further improves the separation rate of electrons and holes and the photocatalytic activity. In addition, during the capture process, NiS2 will also provide active sites for the reaction, which further improves the photocatalytic activity of NiS2 / MoS2 / CdS nanowires. At the same time, the holes generated in the valence band can recombine with the untransferred electrons, or be transmitted to the surface and consumed by the sacrificial agent, which improves the transfer performance of the electrons and further improves the photocatalytic activity.
[0034] The present invention also provides a method for preparing the NiS2 / MoS2 / CdS nanowires described in the above scheme, comprising the following steps:
[0035] The cadmium chloride solution and the sodium diethyldithiocarbamate solution are mixed to carry out a complex reaction to obtain a cadmium complex;
[0036] The cadmium complex is mixed with ethylenediamine to undergo a solvothermal reaction to obtain CdS nanowires;
[0037] The CdS nanowires, nickel nitrate, ammonium molybdate, hexamethylenetetramine and water are mixed and subjected to a hydrothermal reaction to obtain Ni(OH)2 / MoO2 / CdS nanowires;
[0038] The Ni(OH)2 / MoO2 / CdS nanowires are co-calcined with sulfur to obtain the NiS2 / MoS2 / CdS nanowires.
[0039] The present invention mixes a cadmium chloride solution and a sodium diethyldithiocarbamate solution for complex reaction to obtain a cadmium complex. In the present invention, the mass ratio of cadmium chloride in the cadmium chloride solution to sodium diethyldithiocarbamate in the sodium diethyldithiocarbamate solution is preferably 0.06 to 4:1, more preferably 1 to 3:1, and further preferably 1.5 to 2:1. In the present invention, the concentration of the cadmium chloride solution is preferably 0.0010 to 0.040 g / mL, and the concentration of the sodium diethyldithiocarbamate solution is preferably 0.0020 to 0.080 g / mL. In the present invention, the cadmium chloride is preferably 2.5 hydrated cadmium chloride.
[0040] When the cadmium chloride solution and the sodium diethyldithiocarbamate solution are mixed for complex reaction, the cadmium chloride solution is preferably added dropwise to the sodium diethyldithiocarbamate solution. In the present invention, the time of the complex reaction is preferably 0.5 to 1.5 hours, and the complex reaction is preferably carried out under stirring. The complex reaction of the present invention is carried out under stirring conditions to obtain NiS2 / MoS2 / CdS nanowires with uniform particle size. The cadmium complex is a complex of cadmium chloride and sodium diethyldithiocarbamate.
[0041] After the complex reaction, the present invention preferably centrifuges, washes and dries the obtained complex reaction product in sequence to obtain a cadmium complex. The present invention has no particular limitation on the centrifugation and washing, and the unreacted cadmium chloride and sodium diethyldithiocarbamate are fully removed by a scheme well known to those skilled in the art. Specifically, in an embodiment of the present invention, the product is washed multiple times with deionized water and ethanol after centrifugation. The present invention has no particular limitation on the drying, and the product is dried to constant weight by a scheme well known to those skilled in the art. Specifically, in an embodiment of the present invention, the drying is placed in an air drying oven overnight. In the present invention, the color of the cadmium complex is preferably white.
[0042] After obtaining the cadmium complex, the present invention mixes the cadmium complex with ethylenediamine for a solvothermal reaction to obtain CdS nanowires. During the solvothermal reaction, ethylenediamine will undergo a chelation reaction with the cadmium complex. The present invention has no special requirements for the amount of ethylenediamine used, as long as the chelation of the cadmium complex is completed. Specifically, in an embodiment of the present invention, when the amount of 2.5 hydrated cadmium chloride is 170-1020 mg and the amount of sodium diethyldithiocarbamate is 330-2310 mg, the amount of ethylenediamine used is 30 mL. The role of ethylenediamine in the present invention is as a chelating agent and a morphology regulator: ethylenediamine is a strong base and can be selectively adsorbed on a specific crystal plane, inhibiting the growth of the side surface to form a one-dimensional nanowire structure of CdS.
[0043] In the present invention, the temperature of the solvent thermal reaction is preferably 160-200° C., more preferably 180-190° C.; the time is preferably 22-26 h, more preferably 24-25 h.
[0044] After the solvothermal reaction is completed, the present invention preferably centrifuges, washes, and freeze-dries the obtained solvothermal reaction product in sequence to obtain CdS nanowires. The present invention has no special limitation on the centrifugation and washing, and the unreacted raw materials can be fully removed by a scheme well known to those skilled in the art. In the present invention, the freeze drying is preferably carried out in a freeze drying box, and the freeze drying time is preferably 8 to 12 hours, more preferably 9 to 10 hours.
[0045] After obtaining CdS nanowires, the present invention mixes the CdS nanowires, nickel nitrate, ammonium molybdate, hexamethylenetetramine and water and then performs a hydrothermal reaction to obtain Ni(OH)2 / MoO2 / CdS nanowires. In the present invention, the mass ratio of the CdS nanowires to nickel nitrate is preferably 1:0.175-10, more preferably 1:2-8, and further preferably 1:4-6, and the nickel nitrate is preferably nickel nitrate hexahydrate. When cadmium chloride, sodium diethyldithiocarbamate and nickel nitrate are replaced with other compounds, the yield and morphology of NiS2 / MoS2 / CdS nanowires are affected, and none of them are as good as cadmium chloride, sodium diethyldithiocarbamate and nickel nitrate. Among them, some compounds cannot be loaded on CdS nanowires, so NiS2 / MoS2 / CdS nanowires cannot be synthesized. In the present invention, the mass ratio of the CdS nanowires to ammonium molybdate is preferably 1:0.2-12, more preferably 1:2-10, and further preferably 1:4-8; the ammonium molybdate is preferably ammonium molybdate tetrahydrate. If ammonium molybdate is replaced with other molybdates, other metal ions will be introduced, and impurities will be generated in an alkaline environment, affecting the synthesis of the final sample. In the present invention, the mass ratio of the CdS nanowires to hexamethylenetetramine is preferably 1:2-4. Hexamethylenetetramine provides an alkaline environment during the hydrothermal reaction to generate Ni(OH)2. In the present invention, the mass ratio of the CdS nanowires to the volume of water is preferably 0.8-6.8 mg:1 mL.
[0046] When the CdS nanowires, nickel nitrate, ammonium molybdate, hexamethylenetetramine and water are mixed in the present invention, the CdS nanowires are preferably dispersed in the water, and the obtained dispersion is first mixed with nickel nitrate and ammonium molybdate, and then second mixed with hexamethylenetetramine. The present invention has no special limitation on the first mixing and the second mixing, and can be mixed evenly using a scheme familiar to those skilled in the art. Specifically, in the embodiment of the present invention, the first mixing and the second mixing are stirred independently for 5 to 40 minutes. The present invention is conducive to obtaining NiS2 / MoS2 / CdS nanowires of uniform size after the CdS nanowires, nickel nitrate, ammonium molybdate and water are first mixed and then second mixed with hexamethylenetetramine.
[0047] In the present invention, the hydrothermal reaction is preferably carried out in a high temperature reactor. In the present invention, the temperature of the hydrothermal reaction is preferably 130-170°C, more preferably 150-160°C; the time is preferably 8-12h, more preferably 9-10h.
[0048] After the hydrothermal reaction, the present invention preferably removes the supernatant in the obtained hydrothermal reaction product and then sequentially washes, centrifuges and freeze-dries to obtain Ni(OH)2 / MoO2 / CdS nanowires. The present invention has no particular limitation on the washing and centrifugation, and the unreacted raw materials can be fully removed by a scheme well known to those skilled in the art. Specifically, in the embodiment of the present invention, the washing is washing with deionized water three times.
[0049] After obtaining Ni(OH)2 / MoO2 / CdS nanowires, the present invention co-calcines the Ni(OH)2 / MoO2 / CdS nanowires with sulfur to obtain the NiS2 / MoS2 / CdS nanowires. In the present invention, the sulfur is preferably sublimated sulfur. The co-calcination temperature is preferably 350-450°C, more preferably 360-420°C; the holding time is preferably 0.5-1.5h, more preferably 1.8-1.2h. In the present invention, the rate of heating to the co-calcination temperature is preferably 5°C / min. During the co-calcination process, sulfur will become sulfur vapor and react with the Ni(OH)2 / MoO2 / CdS nanowires. The mass ratio of the sulfur to the Ni(OH)2 / MoO2 / CdS nanowire precursor is preferably 10-30:1, more preferably 6-12:1, and further preferably 8-10:1.
[0050] In the present invention, the co-calcination preferably includes placing the Ni(OH)2 / MoO2 / CdS nanowires in a crucible, placing two crucibles filled with sulfur before and after the crucible, and then transferring to a tubular furnace connected to high-purity nitrogen. In the present invention, the mass of sulfur in each crucible is preferably half of the total amount of sulfur.
[0051] The preparation method of the present invention is simple and low in cost. In the prepared NiS2 / MoS2 / CdS nanowires, the NiS2 / MoS2 complex grows tightly on the surface of the CdS nanowires, which makes the NiS2 / MoS2 / CdS nanowire catalyst have high cyclic stability in photocatalytic water decomposition to produce hydrogen and photocatalytic degradation.
[0052] The present invention also provides the use of the NiS2 / MoS2 / CdS nanowires described in the above scheme or the NiS2 / MoS2 / CdS nanowires prepared by the preparation method described in the above scheme as catalysts in decomposing water to produce hydrogen or degrading organic pollutants. In the present invention, the organic pollutants preferably include antibiotics or organic dyes; the organic dyes preferably include reactive red (RR2); the antibiotics preferably include one or more of oxytetracycline (OTC), levofloxacin (LEV), tetracycline hydrochloride (TCH) and norfloxacin (NFX).
[0053] In order to further illustrate the present invention, the NiS2 / MoS2 / CdS nanowires and their preparation methods and applications provided by the present invention are described in detail below in conjunction with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.
[0054] Example 1
[0055] (1) Dissolve 170 mg of cadmium chloride 2.5 hydrate and 330 mg of sodium diethyldithiocarbamate in 50 mL of deionized water to obtain a cadmium chloride solution and a sodium diethyldithiocarbamate solution;
[0056] The cadmium chloride solution is added dropwise to the sodium diethyldithiocarbamate solution, stirred for 0.5 h for complexation reaction, centrifuged, washed with deionized water and ethanol for multiple times, and then placed in a forced air drying oven overnight to obtain a white cadmium complex;
[0057] After adding 30 mL of ethylenediamine to the obtained cadmium complex, the mixture was stirred until a uniform solution was formed and transferred to a 50 mL polytetrafluoroethylene stainless steel autoclave for solvothermal reaction at 160 °C for 22 h.
[0058] After the solvothermal reaction was completed, the autoclave was cooled to room temperature, and the solvothermal reaction product was washed with deionized water and ethanol for multiple times, and then dried by centrifugation and freeze drying for 8 hours to obtain CdS nanowires.
[0059] (2) 25 mg of CdS nanowires were dispersed in 30 mL of water, and the resulting dispersion was mixed with 36 mg of nickel nitrate hexahydrate and 42 mg of ammonium molybdate tetrahydrate, stirred for 5 min, 70 mg of hexamethylenetetramine was added, and stirred for another 20 min, then transferred to a high temperature reactor and subjected to a hydrothermal reaction at 130 °C for 8 h;
[0060] After the hydrothermal reaction is completed, wait for cooling to room temperature, pour out the supernatant, wash three times with deionized water, centrifuge and freeze dry in a freezer for 8 hours to obtain Ni(OH)2 / MoO2 / CdS.
[0061] (3) 37.5 mg of the prepared Ni(OH)2 / MoO2 / CdS was placed in a crucible, and two crucibles containing 375 mg of sublimated sulfur were placed before and after the crucible. The crucible was then transferred to a tubular furnace connected to high-purity nitrogen gas, and the temperature was set to 350°C at a heating rate of 5°C / min. The temperature was kept at this temperature for 1 hour to obtain NiS2 / MoS2 / CdS nanowires.
[0062] The NiS2 / MoS2 / CdS nanowire catalyst has a length of 2 to 5 μm and a diameter of 150 to 200 nm and is a nanowire with a stable structure, high light utilization rate and uniform particle size.
[0063] Example 2
[0064] (1) Dissolve 340 mg of cadmium chloride 2.5 hydrate and 660 mg of sodium diethyldithiocarbamate in 50 mL of deionized water to obtain a cadmium chloride solution and a sodium diethyldithiocarbamate solution;
[0065] The cadmium chloride solution was added dropwise to the sodium diethyldithiocarbamate solution, and the mixture was stirred for 0.75 h for complexation reaction. After centrifugation and multiple washing with deionized water and ethanol, the mixture was placed in a forced air drying oven overnight to obtain a white cadmium complex.
[0066] After adding 30 mL of ethylenediamine to the obtained cadmium complex, the mixture was stirred until a uniform solution was formed and transferred to a 50 mL polytetrafluoroethylene stainless steel autoclave for solvothermal reaction at 180 °C for 24 h.
[0067] After the solvothermal reaction was completed, the autoclave was cooled to room temperature, and the solvothermal reaction product was washed with deionized water and ethanol for multiple times, and then dried by centrifugation and freeze drying for 9.5 hours to obtain CdS nanowires.
[0068] (2) 50 mg of CdS nanowires were dispersed in 30 mL of water, and the resulting dispersion was mixed with 72 mg of nickel nitrate hexahydrate and 84 mg of ammonium molybdate tetrahydrate, stirred for 10 min, 140 mg of hexamethylenetetramine was added, and stirred for another 25 min, and then transferred to a high-temperature reactor for a hydrothermal reaction at 150 ° C for 10 h;
[0069] After the hydrothermal reaction is completed, wait for cooling to room temperature, pour out the supernatant, wash three times with deionized water, centrifuge and freeze dry in a freezer for 9 hours to obtain Ni(OH)2 / MoO2 / CdS.
[0070] (3) 75 mg of the prepared Ni(OH)2 / MoO2 / CdS was placed in a crucible, and two crucibles containing 750 mg of sublimated sulfur were placed before and after the crucible. The crucible was then transferred to a tubular furnace connected to high-purity nitrogen. The temperature was set to 370°C, the heating rate was 5°C / min, and the temperature was kept for 1 hour to obtain NiS2 / MoS2 / CdS nanowires.
[0071] The NiS2 / MoS2 / CdS nanowire catalyst has a length of 2 to 5 μm and a diameter of 150 to 200 nm and is a nanowire with a stable structure, high light utilization rate and uniform particle size.
[0072] Example 3
[0073] (1) 850 mg of cadmium chloride 2.5 hydrate and 1650 mg of sodium diethyldithiocarbamate were dissolved in 50 mL of deionized water to obtain a cadmium chloride solution and a sodium diethyldithiocarbamate solution;
[0074] The cadmium chloride solution was added dropwise to the sodium diethyldithiocarbamate solution, and the mixture was stirred for 1.25 hours for complexation reaction. After centrifugation and multiple washing with deionized water and ethanol, the mixture was placed in a forced air drying oven overnight to obtain a white cadmium complex.
[0075] The obtained cadmium complex was added with 30 mL of ethylenediamine, stirred until a uniform solution was formed, and then transferred to a 50 mL polytetrafluoroethylene stainless steel autoclave for solvothermal reaction at 190 °C for 25 h.
[0076] After the solvothermal reaction was completed, the autoclave was cooled to room temperature, and the solvothermal reaction product was washed with deionized water and ethanol for multiple times, and then centrifuged and dried in a freeze drying oven for 10 hours to obtain CdS nanowires.
[0077] (2) 100 mg of CdS nanowires were dispersed in 30 mL of water, and the resulting dispersion was mixed with 145 mg of nickel nitrate hexahydrate and 170 mg of ammonium molybdate tetrahydrate, stirred for 20 min, 280 mg of hexamethylenetetramine was added, and stirred for another 35 min, then transferred to a high-temperature reactor and subjected to a hydrothermal reaction at 160 ° C for 9 h;
[0078] After the hydrothermal reaction was completed, the mixture was cooled to room temperature, the supernatant was discarded, and the mixture was washed three times with deionized water, centrifuged, and freeze-dried in a freezer for 8.5 h to obtain Ni(OH)2 / MoO2 / CdS.
[0079] (3) 150 mg of the prepared Ni(OH)2 / MoO2 / CdS was placed in a crucible, and two crucibles containing 1500 mg of sublimated sulfur were placed before and after the crucible. The crucible was then transferred to a tubular furnace connected to high-purity nitrogen, and the temperature was set to 400°C, with a heating rate of 5°C / min. The temperature was kept at this temperature for 1.5 h. NiS2 / MoS2 / CdS nanowires were obtained.
[0080] The NiS2 / MoS2 / CdS nanowire catalyst has a length of 2 to 5 μm and a diameter of 150 to 200 nm. It is a nanowire with a stable structure, high light utilization rate and uniform particle size.
[0081] Example 4
[0082] (1) Dissolve 510 mg of cadmium chloride 2.5 hydrate and 990 mg of sodium diethyldithiocarbamate in 50 mL of deionized water to obtain a cadmium chloride solution and a sodium diethyldithiocarbamate solution;
[0083] The cadmium chloride solution is added dropwise to the sodium diethyldithiocarbamate solution, stirred for 1 hour for complexation reaction, centrifuged, washed with deionized water and ethanol for multiple times, and then placed in a forced air drying oven overnight to obtain a white cadmium complex;
[0084] The obtained cadmium complex was added with 30 mL of ethylenediamine, stirred until a uniform solution was formed, and then transferred to a 50 mL polytetrafluoroethylene stainless steel autoclave for solvothermal reaction at 200 °C for 23 h.
[0085] After the solvothermal reaction was completed, the autoclave was cooled to room temperature, and the solvothermal reaction product was washed with deionized water and ethanol for multiple times, and then dried by centrifugation and freeze drying for 9 hours to obtain CdS nanowires.
[0086] (2) 75 mg of CdS nanowires were dispersed in 30 mL of water, and the resulting dispersion was mixed with 110 mg of nickel nitrate hexahydrate and 125 mg of ammonium molybdate tetrahydrate, stirred for 15 min, 210 mg of hexamethylenetetramine was added, and stirred for another 30 min, then transferred to a high-temperature reactor and subjected to a hydrothermal reaction at 140 °C for 11 h;
[0087] After the hydrothermal reaction is completed, wait for cooling to room temperature, pour out the supernatant, wash three times with deionized water, centrifuge and freeze dry in a freezer for 10 hours to obtain Ni(OH)2 / MoO2 / CdS.
[0088] (3) 112.5 mg of the prepared Ni(OH)2 / MoO2 / CdS was placed in a crucible, and two crucibles containing 1125 mg of sublimated sulfur were placed before and after the crucible. The crucible was then transferred to a tubular furnace connected to high-purity nitrogen. The temperature was set to 390°C, the heating rate was 5°C / min, and the temperature was kept for 0.75 h to obtain NiS2 / MoS2 / CdS nanowires.
[0089] The NiS2 / MoS2 / CdS nanowire catalyst has a length of 2 to 5 μm and a diameter of 150 to 200 nm and is a nanowire with a stable structure, high light utilization rate and uniform particle size.
[0090] Example 5
[0091] (1) Dissolve 1190 mg of cadmium chloride 2.5 hydrate and 2310 mg of sodium diethyldithiocarbamate in 50 mL of deionized water to obtain a cadmium chloride solution and a sodium diethyldithiocarbamate solution;
[0092] The cadmium chloride solution was added dropwise to the sodium diethyldithiocarbamate solution, and the mixture was stirred for 1.5 hours for complexation reaction. After centrifugation and multiple washing with deionized water and ethanol, the mixture was placed in a forced air drying oven overnight to obtain a white cadmium complex.
[0093] After adding 30 mL of ethylenediamine to the obtained cadmium complex, the mixture was stirred until a uniform solution was formed and transferred to a 50 mL polytetrafluoroethylene stainless steel autoclave for solvothermal reaction at 185 °C for 26 h.
[0094] After the solvothermal reaction was completed, the autoclave was cooled to room temperature, and the solvothermal reaction product was washed with deionized water and ethanol for multiple times, and then dried by centrifugation and freeze drying oven for 12 hours to obtain CdS nanowires.
[0095] (2) 150 mg of CdS nanowires were dispersed in 30 mL of water, and the resulting dispersion was mixed with 220 mg of nickel nitrate hexahydrate and 255 mg of ammonium molybdate tetrahydrate, stirred for 25 min, 420 mg of hexamethylenetetramine was added, and stirred for another 40 min, then transferred to a high temperature reactor and subjected to a hydrothermal reaction at 170 ° C for 12 h;
[0096] After the hydrothermal reaction is completed, wait for cooling to room temperature, pour out the supernatant, wash three times with deionized water, centrifuge and freeze dry in a freezer for 12 hours to obtain Ni(OH)2 / MoO2 / CdS.
[0097] (3) 235 mg of the prepared Ni(OH)2 / MoO2 / CdS was placed in a crucible, and two crucibles containing 2350 mg of sublimated sulfur were placed before and after the crucible. The crucible was then transferred to a tubular furnace connected to high-purity nitrogen. The temperature was set to 420°C, the heating rate was 5°C / min, and the temperature was kept for 1.25 h to obtain NiS2 / MoS2 / CdS nanowires.
[0098] The NiS2 / MoS2 / CdS nanowire catalyst has a length of 2 to 5 μm and a diameter of 150 to 200 nm and is a nanowire with a stable structure, high light utilization rate and uniform particle size.
[0099] Example 6
[0100] (1) Dissolve 680 mg of cadmium chloride 2.5 hydrate and 1320 mg of sodium diethyldithiocarbamate in 50 mL of deionized water to obtain a cadmium chloride solution and a sodium diethyldithiocarbamate solution;
[0101] The cadmium chloride solution was added dropwise to the sodium diethyldithiocarbamate solution, and the mixture was stirred for 1.25 hours for complexation reaction. After centrifugation and multiple washing with deionized water and ethanol, the mixture was placed in a forced air drying oven overnight to obtain a white cadmium complex.
[0102] After adding 30 mL of ethylenediamine to the obtained cadmium complex, the mixture was stirred until a uniform solution was formed and transferred to a 50 mL polytetrafluoroethylene stainless steel autoclave for solvothermal reaction at 195 °C for 24 h.
[0103] After the solvothermal reaction was completed, the autoclave was cooled to room temperature, and the solvothermal reaction product was washed with deionized water and ethanol for multiple times, and then dried by centrifugation and freeze drying for 10.5 h to obtain CdS nanowires.
[0104] (2) 125 mg of CdS nanowires were dispersed in 30 mL of water, and the resulting dispersion was mixed with 180 mg of nickel nitrate hexahydrate and 210 mg of ammonium molybdate tetrahydrate, stirred for 15 min, 350 mg of hexamethylenetetramine was added, and stirred for another 30 min, then transferred to a high-temperature reactor and subjected to a hydrothermal reaction at 155 °C for 9.5 h;
[0105] After the hydrothermal reaction is completed, wait for cooling to room temperature, pour out the supernatant, wash three times with deionized water, centrifuge and freeze dry in a freezer for 11 hours to obtain Ni(OH)2 / MoO2 / CdS.
[0106] (3) 187.5 mg of the prepared Ni(OH)2 / MoO2 / CdS was placed in a crucible, and two crucibles containing 1875 mg of sublimated sulfur were placed before and after the crucible. The crucible was then transferred to a tubular furnace connected to high-purity nitrogen. The temperature was set to 430°C, the heating rate was 5°C / min, and the temperature was kept for 1 hour to obtain NiS2 / MoS2 / CdS nanowires.
[0107] The NiS2 / MoS2 / CdS nanowire catalyst has a length of 2 to 5 μm and a diameter of 150 to 200 nm and is a nanowire with a stable structure, high light utilization rate and uniform particle size.
[0108] Example 7
[0109] (1) Dissolve 1020 mg of cadmium chloride 2.5 hydrate and 1980 mg of sodium diethyldithiocarbamate in 50 mL of deionized water to obtain a cadmium chloride solution and a sodium diethyldithiocarbamate solution;
[0110] The cadmium chloride solution is added dropwise to the sodium diethyldithiocarbamate solution, stirred for 1 hour for complexation reaction, centrifuged, washed with deionized water and ethanol for multiple times, and then placed in a forced air drying oven overnight to obtain a white cadmium complex;
[0111] After adding 30 mL of ethylenediamine to the obtained cadmium complex, the mixture was stirred until a uniform solution was formed and transferred to a 50 mL polytetrafluoroethylene stainless steel autoclave for solvothermal reaction at 170 °C for 25 h.
[0112] After the solvothermal reaction was completed, the autoclave was cooled to room temperature, and the solvothermal reaction product was washed with deionized water and ethanol for multiple times, and then dried by centrifugation and freeze drying for 9 hours to obtain CdS nanowires.
[0113] (2) 175 mg of CdS nanowires were dispersed in 30 mL of water, and the resulting dispersion was mixed with 255 mg of nickel nitrate hexahydrate and 295 mg of ammonium molybdate tetrahydrate, stirred for 20 min, 490 mg of hexamethylenetetramine was added, and stirred for another 35 min, then transferred to a high-temperature reactor and subjected to a hydrothermal reaction at 165 ° C for 10.5 h;
[0114] After the hydrothermal reaction was completed, the mixture was cooled to room temperature, the supernatant was discarded, and the mixture was washed three times with deionized water. The mixture was centrifuged and freeze-dried in a freeze-drying oven for 11.5 hours to obtain Ni(OH)2 / MoO2 / CdS.
[0115] (3) 270 mg of the prepared Ni(OH)2 / MoO2 / CdS was placed in a crucible, and two crucibles containing 2700 mg of sublimated sulfur were placed before and after the crucible. The crucible was then transferred to a tubular furnace connected to high-purity nitrogen. The temperature was set to 450°C, the heating rate was 5°C / min, and the temperature was kept for 0.75 h to obtain NiS2 / MoS2 / CdS nanowires.
[0116] The NiS2 / MoS2 / CdS nanowire catalyst has a length of 2 to 5 μm and a diameter of 150 to 200 nm and is a nanowire with a stable structure, high light utilization rate and uniform particle size.
[0117] Example 8
[0118] (1) Dissolve 425 mg of cadmium chloride 2.5 hydrate and 825 mg of sodium diethyldithiocarbamate in 50 mL of deionized water to obtain a cadmium chloride solution and a sodium diethyldithiocarbamate solution;
[0119] The cadmium chloride solution is added dropwise to the sodium diethyldithiocarbamate solution, stirred for 0.5 h to carry out complex reaction, centrifuged, washed with deionized water and ethanol for multiple times, and then placed in a forced air drying oven overnight to obtain a white cadmium complex;
[0120] After adding 30 mL of ethylenediamine to the obtained cadmium complex, the mixture was stirred until a uniform solution was formed and transferred to a 50 mL polytetrafluoroethylene stainless steel autoclave for solvothermal reaction at 165 °C for 22 h.
[0121] After the solvothermal reaction was completed, the autoclave was cooled to room temperature, and the solvothermal reaction product was washed with deionized water and ethanol for multiple times, and then dried by centrifugation and freeze drying for 8.5 hours to obtain CdS nanowires.
[0122] (2) 50 mg of CdS nanowires were dispersed in 30 mL of water, and the resulting dispersion was mixed with 72 mg of nickel nitrate hexahydrate and 84 mg of ammonium molybdate tetrahydrate, stirred for 15 min, 140 mg of hexamethylenetetramine was added, and stirred for another 20 min, then transferred to a high-temperature reactor and subjected to a hydrothermal reaction at 145 °C for 8.5 h;
[0123] After the hydrothermal reaction was completed, the mixture was cooled to room temperature, the supernatant was discarded, and the mixture was washed three times with deionized water. The mixture was centrifuged and freeze-dried in a freeze-drying oven for 9.5 hours to obtain Ni(OH)2 / MoO2 / CdS.
[0124] (3) 75 mg of the prepared Ni(OH)2 / MoO2 / CdS was placed in a crucible, and two crucibles containing 750 mg of sublimated sulfur were placed before and after the crucible. The crucible was then transferred to a tubular furnace connected to high-purity nitrogen. The temperature was set to 380°C, the heating rate was 5°C / min, and the temperature was kept for 0.5 h to obtain NiS2 / MoS2 / CdS nanowires.
[0125] The NiS2 / MoS2 / CdS nanowire catalyst has a length of 2 to 5 μm and a diameter of 150 to 200 nm and is a nanowire with a stable structure, high light utilization rate and uniform particle size.
[0126] Example 9
[0127] (1) Dissolve 765 mg of cadmium chloride 2.5 hydrate and 1485 mg of sodium diethyldithiocarbamate in 50 mL of deionized water to obtain a cadmium chloride solution and a sodium diethyldithiocarbamate solution;
[0128] The cadmium chloride solution was added dropwise to the sodium diethyldithiocarbamate solution, and the mixture was stirred for 0.75 h for complexation reaction. After centrifugation and multiple washing with deionized water and ethanol, the mixture was placed in a forced air drying oven overnight to obtain a white cadmium complex.
[0129] After adding 30 mL of ethylenediamine to the obtained cadmium complex, the mixture was stirred until a uniform solution was formed and transferred to a 50 mL polytetrafluoroethylene stainless steel autoclave for solvothermal reaction at 175 °C for 23 h.
[0130] After the solvothermal reaction was completed, the autoclave was cooled to room temperature, and the solvothermal reaction product was washed with deionized water and ethanol for multiple times, and then dried by centrifugation and freeze drying for 11.5 hours to obtain CdS nanowires.
[0131] (2) 100 mg of CdS nanowires were dispersed in 30 mL of water, and the resulting dispersion was mixed with 145 mg of nickel nitrate hexahydrate and 170 mg of ammonium molybdate tetrahydrate, stirred for 10 min, 280 mg of hexamethylenetetramine was added, and stirred for another 25 min, then transferred to a high-temperature reactor and subjected to a hydrothermal reaction at 135 ° C for 11.5 h;
[0132] After the hydrothermal reaction was completed, the mixture was cooled to room temperature, the supernatant was discarded, and the mixture was washed three times with deionized water. The mixture was centrifuged and freeze-dried in a freeze-drying oven for 10.5 h to obtain Ni(OH)2 / MoO2 / CdS.
[0133] (3) 150 mg of the prepared Ni(OH)2 / MoO2 / CdS was placed in a crucible, and two crucibles containing 1500 mg of sublimated sulfur were placed before and after the crucible. The crucible was then transferred to a tubular furnace connected to high-purity nitrogen. The temperature was set to 360°C, the heating rate was 5°C / min, and the temperature was kept for 0.5 h to obtain NiS2 / MoS2 / CdS nanowires.
[0134] The NiS2 / MoS2 / CdS nanowire catalyst has a length of 2 to 5 μm and a diameter of 150 to 200 nm and is a nanowire with a stable structure, high light utilization rate and uniform particle size.
[0135] Example 10
[0136] (1) 935 mg of cadmium chloride 2.5 hydrate and 1815 mg of sodium diethyldithiocarbamate were dissolved in 50 mL of deionized water to obtain a cadmium chloride solution and a sodium diethyldithiocarbamate solution;
[0137] The cadmium chloride solution was added dropwise to the sodium diethyldithiocarbamate solution, and the mixture was stirred for 1.5 hours for complexation reaction. After centrifugation and multiple washing with deionized water and ethanol, the mixture was placed in a forced air drying oven overnight to obtain a white cadmium complex.
[0138] After adding 30 mL of ethylenediamine to the obtained cadmium complex, the mixture was stirred until a uniform solution was formed and transferred to a 50 mL polytetrafluoroethylene stainless steel autoclave for solvothermal reaction at 190 °C for 26 h.
[0139] After the solvothermal reaction was completed, the autoclave was cooled to room temperature, and the solvothermal reaction product was washed with deionized water and ethanol for multiple times, and then dried by centrifugation and freeze drying for 11 hours to obtain CdS nanowires.
[0140] (2) 125 mg of CdS nanowires were dispersed in 30 mL of water, and the resulting dispersion was mixed with 180 mg of nickel nitrate hexahydrate and 210 mg of ammonium molybdate tetrahydrate, stirred for 25 min, 350 mg of hexamethylenetetramine was added, and stirred for another 40 min, then transferred to a high temperature reactor and subjected to a hydrothermal reaction at 150 °C for 10 h;
[0141] After the hydrothermal reaction was completed, the mixture was cooled to room temperature, the supernatant was discarded, and the mixture was washed three times with deionized water. The mixture was centrifuged and freeze-dried in a freeze-drying oven for 9.5 hours to obtain Ni(OH)2 / MoO2 / CdS.
[0142] (3) 187.5 mg of the prepared Ni(OH)2 / MoO2 / CdS was placed in a crucible, and two crucibles containing 1875 mg of sublimated sulfur were placed before and after the crucible. The crucible was then transferred to a tubular furnace connected to high-purity nitrogen. The temperature was set to 410°C, the heating rate was 5°C / min, and the temperature was kept for 1.25 h to obtain NiS2 / MoS2 / CdS nanowires.
[0143] The NiS2 / MoS2 / CdS nanowire catalyst has a length of 2 to 5 μm and a diameter of 150 to 200 nm and is a nanowire with a stable structure, high light utilization rate and uniform particle size.
[0144] Comparative Example 1
[0145] The preparation of NiS2 / CdS nanowires is different from the preparation of NiS2 / MoS2 / CdS nanowires in Example 3 only in that ammonium molybdate is not added.
[0146] Comparative Example 2
[0147] The preparation of NiS2 / MoS2 is different from the preparation of NiS2 / MoS2 / CdS nanowires in Example 3 only in that CdS nanowires are not added, and the other steps remain unchanged.
[0148] Figure 1 The XRD comparison diagram of the CdS nanowire in Example 10, the NiS2 / MoS2 in Comparative Example 2, and the NiS2 / MoS2 / CdS nanowire (NMC) in Example 10 is shown in FIG. Figure 1 It can be seen that the NiS2 / MoS2 / CdS nanowires of the present invention have characteristic peaks of CdS and NiS2 / MoS2 at the same time, and the positions of the peaks are not offset, and no other miscellaneous peaks appear. After NiS2 / MoS2 and CdS are compounded, the peak position of CdS does not change, indicating the successful preparation of NiS2 / MoS2 / CdS, and indicating that the addition of NiS2 / MoS2 has no effect on the crystal phase structure of CdS.
[0149] The performance of the NiS2 / MoS2 / CdS nanowires in Example 3 was evaluated using the Zhongjiao Jinyuan photocatalytic activity online evaluation system. Figure 2 As shown. Figure 2 It can be seen that the prepared NiS2 / MoS2 / CdS nanowire catalyst has excellent photocatalytic performance in decomposing water to produce hydrogen under visible light irradiation, with a hydrogen production performance of up to 8542 μmol g -1 ·h -1 .
[0150] The photocatalytic degradation performance of the NiS2 / MoS2 / CdS nanowires of Example 3 was evaluated. The process is as follows:
[0151] Prepare 20 ppm solutions of oxytetracycline (OTC), tetracycline hydrochloride (TCH), levofloxacin (LEF), norfloxacin (NFX) and reactive red 2 (RR2). Take 25 mL of the above solutions and 25 mg of NiS2 / MoS2 / CdS nanowires of Example 3 in a clean beaker. Perform light-free treatment and stir for 30 minutes to establish desorption-adsorption equilibrium.
[0152] Transfer the above solution to a double-layer quartz reactor with water inlet and outlet. Wrap the reactor with tin foil, place a 300W xenon lamp above the reactor, turn on the cooling water, turn on the light, and start timing. Take a sample every 10 minutes, take 3mL each time, centrifuge, absorb the upper clear liquid, and quickly test it using a UV spectrophotometer. Measure the absorption value at the maximum absorption wavelength of the original solution and obtain a curve of absorption value and time. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that the prepared NiS2 / MoS2 / CdS nanowire catalyst can effectively degrade oxytetracycline, tetracycline hydrochloride, levofloxacin, norfloxacin, and reactive red 2 in water, with a degradation rate of 76% to 93% and a concentration range of 20 ppm.
[0153] The photocatalytic degradation performance of Example 3 was evaluated by the above-mentioned photocatalytic degradation performance test method. Figure 4 It can be seen that the prepared NiS2 / MoS2 / CdS nanowire catalyst can still have good degradation performance and good stability after being cycled four times.
[0154] The NiS2 / MoS2 / CdS nanowires of Example 10 were subjected to SEM analysis and high-resolution transmission electron microscopy analysis. The results are as follows: Figures 5-6 As shown. Figures 5-6 It can be seen that the NiS2 / MoS2 composite is attached to the CdS nanowire; the NiS2 / MoS2 composite is a nanosheet structure with a sheet diameter of 30 to 50 nm.
[0155] The performance of the CdS nanowires of Example 3, the NiS2 / MoS2 / CdS nanowires of Example 3, the NiS2 / CdS nanowires of Comparative Example 1, and the NiS2 / MoS2 of Comparative Example 2 were evaluated using an online photocatalytic activity evaluation system. The specific process was the same as above. The results are shown in FIG. Figure 7 As shown. Figure 7 It can be seen that NiS2 / MoS2 / CdS has the best hydrogen production performance, with a hydrogen production of 213 times that of pure CdS and 4.6 times that of NiS2 / CdS. The hydrogen production of NiS2 / MoS2 is 0.
[0156] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A NiS2 / MoS2 / CdS nanowire, comprising a CdS nanowire and a NiS2 / MoS2 composite loaded on the CdS nanowire; the NiS2 / MoS2 composite comprises NiS2 and MoS2; the loading amount of the NiS2 / MoS2 composite is 35-50wt%; the molar ratio of NiS2 to MoS2 in the NiS2 / MoS2 composite is 1:0.2-3.
2. The NiS2 / MoS2 / CdS nanowire according to claim 1, characterized in that: The length of the NiS2 / MoS2 / CdS nanowire is 2-5 μm, and the diameter is 150-200 nm.
3. The method for preparing NiS2 / MoS2 / CdS nanowires according to any one of claims 1 to 2, characterized in that: The following steps are involved: The cadmium chloride solution and the sodium diethyldithiocarbamate solution are mixed for complexation reaction to obtain a cadmium complex; the mass ratio of cadmium chloride in the cadmium chloride solution to sodium diethyldithiocarbamate in the sodium diethyldithiocarbamate solution is 0.06 to 4:1; The cadmium complex is mixed with ethylenediamine to undergo a solvothermal reaction to obtain CdS nanowires; the solvothermal reaction is performed at a temperature of 160 to 200° C. and for a time of 22 to 26 hours; The CdS nanowires, nickel nitrate, ammonium molybdate, hexamethylenetetramine and water are mixed and subjected to a hydrothermal reaction to obtain Ni(OH)2 / MoO2 / CdS nanowires; the mass ratio of the CdS nanowires to ammonium molybdate is 1:0.2-12; The mass ratio of CdS nanowires to hexamethylenetetramine is 1:2-4; the temperature of the hydrothermal reaction is 130-170° C., and the time is 8-12 hours; Co-calcining the Ni(OH)2 / MoO2 / CdS nanowires with sulfur to obtain the NiS2 / MoS2 / CdS nanowires; The mass ratio of the CdS nanowires to nickel nitrate is 1:0.175-10; the co-calcination temperature is 350-450° C., and the heat preservation time is 0.5-1.5 h.
Citation Information
Patent Citations
Preparation method and application of Ni / Ni3C / CdS nanowire catalyst with photocatalytic performance
CN113181942A